Strigo-D2: a bio-sensor for monitoring spatio-temporal strigolactone signaling patterns in intact plants - Song, Changzheng; Zhao, Jiao; Guichard, Marjorie; Shi, Dongbo; Großmann, Guido; Schmitt, Christian; Jouannet, Virginie; Greb, Thomas (Plant physiology, 2022)
Strigolactones (SLs) are a class of plant hormones that mediate biotic interactions and modulate developmental programs in response to endogenous and exogenous stimuli. However, a comprehensive view on the spatio-temporal pattern of SL signaling has not been established, and tools for a systematic in planta analysis do not exist. Here, we present Strigo-D2, a genetically encoded ratiometric SL signaling sensor that enables the examination of SL signaling distribution at cellular resolution and is capable of rapid response to altered SL levels in intact Arabidopsis (Arabidopsis thaliana) plants. By monitoring the abundance of a truncated and fluorescently labeled SUPPRESSOR OF MAX2 1-LIKE 6 (SMXL6) protein, a proteolytic target of the SL signaling machinery, we show that all cell types investigated have the capacity to respond to changes in SL levels but with very different dynamics. In particular, SL signaling is pronounced in vascular cells but low in guard cells and the meristematic region of the root. We also show that other hormones leave Strigo-D2 activity unchanged, indicating that initial SL signaling steps work in isolation from other hormonal signaling pathways. The specificity and spatio-temporal resolution of Strigo-D2 underline the value of the sensor for monitoring SL signaling in a broad range of biological contexts with highly instructive analytical depth.
Published: 29 October 2021
Gesehen am 07.07.2022